Bimbingan Belajar Olimpiade Sains Nasional (OSN) Matematika Siswa di SMPN 3 Batusangkar - Putri, Jeni Tri; Alberianto, Alberianto; Yuberta, Kurnia Rahmi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
The national mathematics science olympiads in junior high schools in the mathematics branch have an important role in the world of education by providing students with the ability to understand, apply and appreciate mathematical concepts in a scientific context. This includes developing a deeper understanding of mathematics, understanding of the scientific method, the ability to think logically, effective communication skills, and the ability to solve problems. This discussion details how the national science Olympiad helps students become individuals who are experts in mathematics and ready to play a role in science, technology and society.Â